Il frastuono della metafisica. Linguaggio e tecnica nel pensiero di Martin Heidegger - Spina, Salvatore (Mechane, 2024)
The paper aims to analyze the relationship between language and technology in Heidegger’s works. Both the questions have an ontological dimension: the language is designated by Heidegger as ‘the house of Being’ and the technology is the way, in which Being (not) appears in the Modernity. The modern affirmation of technology sets a radical transformation in the shape of language. It becomes communication and information – technological language – and ‘misses’ its original relationship with the dimension of Being. I will analyze this historical and ontological change to finally hint at a kind of language beyond the metaphysical determinations.